Peran Guru Akidah Akhlak dalam Menciptakan Kreativitas Pembelajaran di MTS Al-Khairiyah Badamussalam Kasemen Serang Banten - Khairul Ikhwan (PT. Pusmedia Group Indonesia, 2023)
Creative teachers are those who know how to use different methods in an innovative way to guide students and guide the learning process. In addition, teacher creativity is also reflected in their participation in daily creative activities which is considered a positive aspect of their role. On the other hand, if teachers do not show their creativity in learning, it will have a big impact and even hinder the development of students' creativity. This research was conducted using a field survey method at MTS Al-Khairiyah Badamussalam in Kasemen, Serang City, Banten. The research results show that a Aqidah Akhlaq teacher at MTS Al-Khairiyah Badamussalam uses creative learning methods in meetings, such as project-based learning, question and answer education and blended education. Subject-specific videos, LKS and LKPD books and the internet are used as learning tools. Student assignments include preparing extracts and answering written and oral questions. Factors that support creativity in learning include the philosophy of providing adequate facilities such as the internet, computer laboratories and projectors. However, the limited number of computers hinders teacher creativity in carrying out the learning process. Keywords: Teacher's role; Akidah Akhlak; Learning creativity.